Phytate Intake, Health and Disease: "Let Thy Food Be Thy Medicine and Medicine Be Thy Food" - Antelm Pujol; Pilar Sanchis; Felix Grases; Luis Masmiquel (MDPI AG, 2023)
Phytate (myo-inositol hexakisphosphate or InsP6) is the main phosphorus reservoir that is present in almost all wholegrains, legumes, and oilseeds. It is a major component of the Mediterranean and Dietary Approaches to Stop Hypertension (DASH) diets. Phytate is recognized as a nutraceutical and is classified by the Food and Drug Administration (FDA) as Generally Recognized As Safe (GRAS). Phytate has been shown to be effective in treating or preventing certain diseases. Phytate has been shown to inhibit calcium salt crystallization and, therefore, to reduce vascular calcifications, calcium renal calculi and soft tissue calcifications. Moreover, the adsorption of phytate to the crystal faces can inhibit hydroxyapatite dissolution and bone resorption, thereby playing a role in the treatment/prevention of bone mass loss. Phytate has a potent antioxidation and anti-inflammatory action. It is capable of inhibiting lipid peroxidation through iron chelation, reducing iron-related free radical generation. As this has the effect of mitigating neuronal damage and loss, phytate shows promise in the treatment/prevention of neurodegenerative disease. It is reported that phytate improves lipid and carbohydrate metabolism, increases adiponectin, decreases leptin and reduces protein glycation, which is linked with macrovascular and microvascular diabetes complications. In this review, we summarize the benefits of phytate intake as seen in in vitro, animal model, epidemiological and clinical trials, and we also identify questions to answer in the future.